Liquid Chromatography – Tandem Mass Spectrometry for the Simultaneous Quantitation of Glipizide, Cilostazol and its Active Metabolite 3, 4-dehydro-cilostazol in Rat Plasma: Application for a Pharmacokinetic Study - Satheeshmanikandan, T.R. S.; Sridhar, V.; Kanthikiran, V.V. S.; Swaroopkumar, V.V. S.; Mukkanti, K. (Arzneimittelforschung, 2012)
A liquid chromatography-electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) method for the simultaneous quantitation of glipizide, cilostazol and 3, 4-dehydro-cilostazol in rat plasma was developed and validated. Glimepride was used as an internal standard (IS). The analytes were extracted by using liquid-liquid extraction procedure and separated on a reverse phase C18 column (50 mm×4.6 mm i. d., 5 µ) using acetonitrile: 2 mM ammonium acetate buffer, pH 3.2 (90:10, v/v) as mobile phase at a flow rate 0.4 mL/min in an isocratic mode. Selective reaction monitoring was performed using the transitions m/z 446.4>321.1, 370.2>288.3, 368.3>286.2, and 491.4>352.2 to quantify glipizide, cilostazol, 3, 4-dehydro-cilostazol and glimepride, respectively. Calibration curves were constructed over the range of 25–2 000 ng/mL for glipizide, cilostazol and 3, 4-dehydro-cilostazol. The lower limit of quantitation was 25 ng/mL for all the analytes. The recoveries from spiked control samples were>76% for all analytes and internal standard. Intra and inter day accuracy and precision of validated method were within the acceptable limits of at all concentration. The quantitation method was successfully applied for simultaneous estimation of glipizide, cilostazol and 3, 4-dehydro-cilostazol in a pharmacokinetic drug-drug interaction study in wistar rats.
Keywords: glipizide plasma; gilostazol plasma; 3, 4-dehydro-cilostazol plasma; pharmacokinetics; LC-MS/MS